Impact of Workplace Stressors on Employee Burnout: A Survey on Diversified Professionals - Pandey, Dhruba Lal; Risal, Nischal (Molung Educational Frontier, 2023)
The study has focused on the impact of workplace stressors explained byworkload, work hours, unsupportive supervisors, and unfair treatment on employee burnout. The study adopted a quantitative research approach using a survey method. Professional employees of different sectors have been considered as the population. The 115 usable samples have been taken for the study purpose. The sample has been taken purposively. Five Point Likert Scale and multiple-choice questionnaire have been used for the collection of the data. Questionnaires have been administered online. SPSS and Microsoft Excel software has been used to analyze data. However, data were analyzed using correlation analysis and multiple regression analysis. The study results suggest that work hours are the major predictor of employee burnout among Nepalese professional employees, and workload, unfair treatment, and unsupportive supervisors have negligible contributions to the burnout of Nepalese professional employees.